Law Enforcement Through Judicial Institutions Within The Indonesian Constitutional System - Minanoer Rachman (Yuridika, 2026)
Fundamentally, the execution of a Court Decision that has attained permanent legal force (inkracht van gewijsde) constitutes the final stage in the sequence of litigation proceedings within judicial institutions. However, decisions eligible for immediate execution (uitvoerbaar bij voorraad), as stipulated under Article 180 paragraph (1) of the Herzien Inlandsch Reglement (HIR), may be enforced prematurely. This applies even if the decision has not yet become final and binding due to the losing party pursuing legal remedies such as verzet (opposition), appeal, or cassation. In practice, however, losing parties often demonstrate a lack of voluntary compliance in fulfilling the obligations dictated by a Court Decision. Consequently, intervention from an external authority is necessitated; in this context, the court is legally empowered to "compel" the losing party to execute the judgment. This research examines the extent of the judiciary's role in presiding over executions to safeguard the interests of the litigants. It is observed that judges, in their capacity as executors, tend to prioritize formalistic procedures, which often leads to procedural inefficiency. This creates a risk of protracted execution timelines, further exacerbated by a rigid adherence to redundant formalities. The research methodology employed to address these issues includes the statute approach, the conceptual approach (utilizing legal theories from scholars), and the case approach (analyzing prior court rulings).